FAKTOR RISIKO KEJADIAN PERSALINAN PREMATUR DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2010-2013 - Fransiska Simbolon; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Preterm birth is the birth of a baby of less than 37 weeks gestational age (between 20-37 weeks). Preterm birth is the leading cause of newborn and the second leading cause of death after pneumonia in children under five years. According to the WHO (World Health Organization), every year, an estimated 15 million babies are born preterm, and this number is rising. This study aimed to determine the risk factors of preterm birth at Pirngadi General Hospital Medan in 2012-2013. This is an observational study with case control methode. Sample consisted of 50 women with preterm birth ( cases) and 50 women with aterm birth (control). The variables analyzed are education, employment, parity, history of abortion, pregnancy spacing, completeness of ANC (antenatal care), anemia, hypertension, and nutritional status. Data was analyzed with bivariate analysis by using the chi-square. The result showed that significant risk factors for preterm birth were history of abortion (OR=3,5; 95% CI:1,152-10,633), pregnancy spacing (OR=6,7; 95% CI:1,416-32,367), anemia (OR=4,9; 95% CI:1,503-16,157), nutritional status (OR=7,9; 95% CI:0,943-67,456). Education, employment, parity, frequency of antenatal care, and hypertension were not significant risk factors for preterm birth. Health care workers are expected to improve counseling for pregnant women about the importance of prenatal and to provide antenatal care services according to the standard. Pregnant women should be expected to know the risks of preterm factors as early as possible to prevent and reduce the incidence of preterm birth. Pirngadi General Hospital Pirngadi expected to make the complete and correct recording and reporting. Keywords :Preterm Birth, Risk Factors, Pirngadi General Hospital Medan